Pendidikan Vokasional Warga Belajar Paket C Melalui Pelatihan Painting on The Shirt Sebagai Upaya Memotivasi Berwirausaha - A.T. Hendrawijaya; Lutfi Ariefianto; Fuad Hasan (Fakultas Teknik Universitas Cenderawasih, 2023)
It is necessary to build awareness to foster entrepreneurial motivation among the community at large, especially in the Study Group of Packages C citizens in the Technical Implementation Unit of the Education Office of the Bondowoso Regency Learning Activity Studio (SKB). Given that motivation is one of the drivers of the growth and development of a person's entrepreneurial spirit, one of the most needed motivations is the desire to continue learning and adding skills. Therefore, in order for the learning community to improve their welfare, insight into entrepreneurship is needed, so that through counseling on entrepreneurial motivation, it is hoped that the learning community can foster an entrepreneurial spirit and develop creativity and innovation in entrepreneurship so that it can be used as a provision in their lives. This service activity was carried out at the Technical Implementation Unit of the Bondowoso Regency Learning Activity Center education office, which was located in the SKB Hall. The objectives of this community service are (1) to provide insight and knowledge about the importance of fostering entrepreneurial motivation; (2) to provide insight and knowledge about the importance of developing an entrepreneurial spirit; (3) to develop creativity and innovation in entrepreneurship. The methods used are lecture, question and answer and discussion methods. the results achieved by the service activities are the provision of insights and knowledge about the importance of entrepreneurship for learning citizens pursuing package C in the Technical Implementation Unit of the Education Office of the Bondowoso Regency Learning Activity Center. Thus, through counseling, the learning community of pursuing package C is motivated to become entrepreneurs. Seeing the responses given by participants who are so positive and enthusiastic, shows that this activity is quite high and needs to be followed up with further activities, for that, it needs to be carried out periodically and continuously.